Новые виды яйцеедов-теленомин (Hymenoptera, Scelionidae, Telenominae) фауны СССР. Сообщение 2 - Козлов, М.А.; Кононова, С.В. (Вестник зоологии, 1987)
Five Telenominae species are described as new from the USSR territory: Telenomus algericus sp. n., T. alternator sp. n., T. algiricus sp. n., T. carbonarius sp. n., T. albatorius sp. n. A comparative morphology analysis is given. Type material is deposited in the Zoological Institute (Leningrad), a part of T. albatorius paratypes - in Schmalhausen Institute of Zoology (Kiev).